Time Series Analysis of Performance Efficiency of MCB Bank Limited (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2017)
This research investigates the Time Series Analysis of Performance efficiency  of MCB Bank Limited. Data were collected from Primary as well as secondary sources from management of commercial banks and from SBP officials comprising middle and top management, a closed ended questionnaire.  It was revealed that As stated by the findings, five a considerable length of time Normal proportion about MCB is 81. 20%, which will be higher after that the business Normal. This indicates the execution from claiming MCB will be similarly finer as contrasted with those Normal of UBL, which might have been attempting openly division At as of late privatized. Same time those execution from claiming UBL may be superior At that point ABL which might have been handy in the begin However fair for administration issue Previously, 1999. This demonstrates that UBL need Additionally carried out great its possessions to fill in Be that not finer after that MCB.